Correlation between growth form and movement and their dependence on neuronal age - Argiro, V (J Neurosci, 1984)
Neurites of superior cervical ganglion neurons from embryonic, perinatal, and adult rats extended at different rates when placed in tissue culture on similar collagen substrata. Using high resolution cinematography and a time-lapse video recording system, we concluded that these differences arise from variations in individual growth cone behavior. Growth cones of embryonic and perinatal neuronal origin exhibited high peak rates of advance and filopodial and lamellipodial excresences. Perinatal cones differed from embryonic ones in that they were somewhat larger, advanced in straighter paths, and retracted less, consequently translocating at 14 to 29 microns/hr compared with 8 to 22 microns/hr for embryonic cones (ranges of 4-hr means). The growth cones of neurons obtained from adult rats had scant cytoplasm and short branched filopodia, lacked definitive lamellipodia, and traversed the terrain at 4 to 13 microns/hr due to lack of high peak rates of advance and more time spent in stationary or minimal advance phases. Periodic pauses lasting 10 to 20 min, occurring every 20 to 90 min, interrupted the forward advance of growth cones of all ages. During pauses or slow forward movement, the growth cone displayed numerous filopodia whereas, during brief episodes when embryonic and perinatal growth cones moved at peak rates of 200 microns/hr or more, the cone periphery was predominantly lamellipodial. We conclude that the predominance of a lamellipodial or filopodial conformation correlates with the rate of growth cone advance and that age-dependent variations in neurite extension rates are related to differences in growth cone form and pattern of translocation. This is the first documentation of differing behavior of single growth cones of neurons of varying developmental ages in culture.